2019
DOI: 10.1002/1878-0261.12478
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor suppressor miRNAs by integrative miRNA and mRNA sequencing of matched tumor–normal samples in lung adenocarcinoma

Abstract: The roles of miRNAs in lung cancer have not yet been explored systematically at the genome scale despite their important regulatory functions. Here, we report an integrative analysis of miRNA and mRNA sequencing data for matched tumor–normal samples from 109 Korean female patients with non‐small‐cell lung adenocarcinoma (LUAD). We produced miRNA sequencing (miRNA‐Seq) and RNA‐Seq data for 48 patients and RNA‐Seq data for 61 additional patients. Subsequent differential expression analysis with stringent criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
0
36
1
Order By: Relevance
“…Although miR‐338‐5p had been reported to be downregulated in non‐small‐cell lung carcinoma and glioblastoma, we have found that its expression was reduced in the majority of ESCC. Analysis of GEO datasets showed the same phenomenon in gastric, colon, and rectal cancers, thus suggesting that miR‐338‐5p has tumor suppressor functions in the gastrointestinal tract.…”
Section: Discussioncontrasting
confidence: 58%
“…Although miR‐338‐5p had been reported to be downregulated in non‐small‐cell lung carcinoma and glioblastoma, we have found that its expression was reduced in the majority of ESCC. Analysis of GEO datasets showed the same phenomenon in gastric, colon, and rectal cancers, thus suggesting that miR‐338‐5p has tumor suppressor functions in the gastrointestinal tract.…”
Section: Discussioncontrasting
confidence: 58%
“…Next-generation sequencing and expression analysis of miRNAs in PTC and contralateral normal thyroid tissue specimens revealed miR-30a-3p to be among the most abundantly downregulated miRNAs in PTC [32]. Significantly decreased level of miR-30a-3p in tumor tissue compared to corresponding non-tumor tissue was also found in lung carcinoma [7,8,10,26], esophageal carcinoma [27], gastric cancer [28], colorectal cancer [14] and liver cancer [18].…”
Section: Discussionmentioning
confidence: 95%
“…One of the microRNAs with potential tumor suppressor activity that is frequently found to be deregulated and associated with aggressive tumor features and progression in various human cancers is miR-30a-3p. So far, downregulated expression of this member of the miR-30 family has been reported in lung cancer [7][8][9][10], breast cancer [11][12][13], colorectal cancer [14], bladder cancer [15], ovarian cancer [16], endometrial cancer [17], hepatocellular carcinoma [18], hematologic malignancies [19] and others.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs play an important role in cell functions in most biological processes. Typical miRNAs negatively regulate the expression of multiple target genes 6 . Abnormalities in miRNAs may result in abnormal conditions such as microglial hyperactivation, persistent neuroinflammation and abnormal polarization of brain macrophages, which may contribute to the pathogenesis of neurological diseases such as glioma, ischemia and SCI 7 .…”
Section: Introductionmentioning
confidence: 99%